Navigating Hindu Family and Christian Belief: An Ethnography of Christian Prayer Meetings in a Kolkata Neighbourhood - Dasgupta, Abhijit (International journal of Asian christianity, 2024)
The paper is an ethnographic study of an urban Bengali Christian neighbourhood in Kolkata where Hindu women from nearby places attend the two Christian prayer meetings – Catholic and Pentecostal – run by the local preachers of the neighbourhood. Borrowing the theoretical understanding of belief, the paper interrogates the question, posed by Cannell (2006) ‘what difference does Christianity make, in the lives of these Hindu women? The paper looks into the experiences of these women in the intimate spaces of kinship, marriage and family as they undergo a form of separation from their Hindu beliefs yet remain largely embedded within Hindu familial ties and obligations without engaging in the practice of baptismal conversion. The study allows us to critically examine the sharp binaries of religious divisions and argues that a focus on baptismal conversion only renders invisible the complex possibilities of what difference Christianity makes on the ground.